2018
DOI: 10.1038/s41385-018-0060-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling reveals monocyte-related macrophages phenotypically resembling DC in human intestine

Abstract: The tissue dendritic cell (DC) compartment is heterogeneous, and the ontogeny and functional specialization of human tissue conventional DC (cDC) subsets and their relationship with monocytes is unresolved. Here we identify monocyte-related CSF1RFlt3 antigen presenting cells (APCs) that constitute about half of the cells classically defined as SIRPα DCs in the steady-state human small intestine. CSF1RFlt3 APCs express calprotectin and very low levels of CD14, are transcriptionally related to monocyte-derived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 60 publications
1
53
0
Order By: Relevance
“…It is likely that this treatment also affects the T cell numbers in the periphery. Second, solid organ transplantation surgery causes ischemia and reperfusion injury of the graft that increases the turnover of leukocytes (Eguiluz-Gracia et al, 2016); and third, our previous studies have shown that dendritic cells and some of the macrophage subsets are rapidly replaced in the transplanted duodenum Richter et al, 2018), thereby increasing the risk of local allo-reactivity. As shown by Zuber et al (Zuber et al, 2016) Most studies of SI CD8 T cells in humans have focused on the intraepithelial compartment, and there is less knowledge about the CD8 T cell population in LP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that this treatment also affects the T cell numbers in the periphery. Second, solid organ transplantation surgery causes ischemia and reperfusion injury of the graft that increases the turnover of leukocytes (Eguiluz-Gracia et al, 2016); and third, our previous studies have shown that dendritic cells and some of the macrophage subsets are rapidly replaced in the transplanted duodenum Richter et al, 2018), thereby increasing the risk of local allo-reactivity. As shown by Zuber et al (Zuber et al, 2016) Most studies of SI CD8 T cells in humans have focused on the intraepithelial compartment, and there is less knowledge about the CD8 T cell population in LP.…”
Section: Discussionmentioning
confidence: 99%
“…Small intestinal samples were either obtained during pancreatic cancer surgery (Whipple procedure, n = 35; mean age 63yr; range 40-81yr; 16 female), or from donors and/or patients during pancreas-duodenum transplantation (donors: n = 52; mean age 31yr; range 5-55yr; 24 female; patients: n = 36; mean age 41yr; range 25-60yr; 14 female) as described previously (Landsverk et al, 2017;Richter et al, 2018). Endoscopic biopsies from donor and patient duodenum were obtained 3, 6 and 52 weeks after transplantation.…”
Section: Human Biological Materialmentioning
confidence: 99%
“…Human biological material SI samples were obtained either during pancreatic cancer surgery (Whipple procedure, n = 35; mean age 63 yr, range 40-81; 16 female) or from donors or patients during pancreas-duodenum Tx (donors, n = 52; mean age 31 yr, range 5-55; 24 female; patients, n = 36; mean age 41 yr, range 25-60; 14 female) as described previously (Landsverk et al, 2017;Richter et al, 2018). Cancer patients receiving neoadjuvant chemotherapy were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…The first step to characterize intestinal Mfs by flow cytometry is gating on MNPs, i.e., CD45 + Lin −(CD3/CD19/CD56) HLA-DR int−hi CD14 neg−hi cells (Figures 3A, 4). Then, among MNPs, CD14 (Figures 3A, 4), CD64 and CD163 are used to distinguish Mfs from DCs (72,75,(221)(222)(223)(224)(225). To note, various studies have shown that CD64 alone was not sufficient to distinguish intestinal Mfs from DCs, as some cDC2 are CD64 + (72,135,220,224).…”
Section: Phenotype and Frequency Of Intestinal Mucosa Macrophagesmentioning
confidence: 99%